1996
DOI: 10.1103/physrevb.54.r3683
|View full text |Cite
|
Sign up to set email alerts
|

Spatially and temporally resolved emission from aggregates in conjugated polymers

Abstract: We present results of cw, time-resolved, and spatially resolved spectroscopic studies of emission and absorption in a model conjugated polymer, poly( p-pyridyl vinylene͒ ͑PPyV͒. The redshifted film spectra suggest the formation of aggregated regions. The ϳ4ϫ reduction in emission efficiency in films vs solution is attributed to a longer radiative lifetime for aggregate excitons, as is evidenced by time-resolved fluorescence measurements. We present direct optical imaging of aggregates in a conjugated polymer v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
99
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(105 citation statements)
references
References 24 publications
6
99
0
Order By: Relevance
“…[6][7][8] The presence of interchain electronic species has important implications for the performance of devices based on these materials: interchain species may be responsible for quenching a conjugated polymer's luminescence but also may be beneficial for promoting charge transport. [9][10][11] There is also debate concerning the physical nature of interchain electronic species, which are often referred to in the literature as "excimers", 8,[12][13][14] "aggregrates", 9,[15][16][17][18][19][20] or "polaron pairs". [6][7][8][21][22][23] The way that we distinguish among these labels is to use "excimer" to denote a neutral excitation shared equally between two or more chromophores in the electronic excited state and "aggregate" to imply delocalization of the wave function over multiple chain segments in both the ground and excited states.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8] The presence of interchain electronic species has important implications for the performance of devices based on these materials: interchain species may be responsible for quenching a conjugated polymer's luminescence but also may be beneficial for promoting charge transport. [9][10][11] There is also debate concerning the physical nature of interchain electronic species, which are often referred to in the literature as "excimers", 8,[12][13][14] "aggregrates", 9,[15][16][17][18][19][20] or "polaron pairs". [6][7][8][21][22][23] The way that we distinguish among these labels is to use "excimer" to denote a neutral excitation shared equally between two or more chromophores in the electronic excited state and "aggregate" to imply delocalization of the wave function over multiple chain segments in both the ground and excited states.…”
Section: Introductionmentioning
confidence: 99%
“…6,8,21 In films of some conjugated polymers, the presence of a weak absorption band that is red-shifted from that of a single chain provides evidence that interchain species (aggregates) also can form in the ground electronic state. 9,16,18,28 While all of these studies have provided some understanding regarding the dynamics of interchain species and their effects on luminescence quantum yields, there is still relatively little known concerning the electronic nature of the intermolecular excited state, and which of the various interchain labels, if any, is most appropriate.…”
Section: Introductionmentioning
confidence: 99%
“…Excitation of the aggregate band typically produces a broad, featureless and highly Stokes-shifted emission. Studies of laddertype poly(para-phenylene), [20][21][22] poly(para-pyridyl vinylene), 23,24 and polyfluorene 25 deriviatives show strong evidence for aggregate formation in films. Near-field scanning optical microscopy (NSOM) shows that the optical properties of these films vary from location to location, consistent with the idea of spatially localized aggregate species.…”
Section: Introductionmentioning
confidence: 99%
“…Being a large class of fluorescent pigment, cyanine dye has been used extensively in photosensitization, nonlinear optics, biological fluorescent detection, biomedicine and photodynamic therapy of tumor [41][42][43][44][45]. It is reported that cyanine dye MTC, 3,3′-di(3-sulfo-propyl)-4,5,4′,5′-dibenzo-9-methylthiacarbocyanine triethylammonium salt ( as shown in Figure 2(a)), is an excellent G-quadruplex ligand and could present significant spectral changes and strong fluorescent enhancement when binding to specific G-quadruplex [46].…”
mentioning
confidence: 99%